2018
DOI: 10.1111/aor.13331
|View full text |Cite
|
Sign up to set email alerts
|

VA‐ECMO Support in Nonsurgical Patients With Refractory Cardiogenic Shock: Pre‐Implant Outcome Predictors

Abstract: Refractory cardiogenic shock (RCS) is associated with a high mortality. Veno-arterial extracorporeal membrane oxygenation (VA-ECMO) is increasingly used as acute cardiopulmonary support but selection of VA-ECMO candidates remains challenging. There are limited data on which pre-VA-ECMO variables that predict outcome. The aim of this study was to identify pre-VA-ECMO predictors of 90-day mortality. We retrospectively analyzed 76 consecutive patients (median age 52; interquartile range [IQR]: 37-60) supported wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 43 publications
4
24
0
Order By: Relevance
“…While there were several variables on univariate analysis suggestive of 30‐day survival in our study such as BMI, serum creatinine, platelet count, and SYNTAX score, the only measured multivariable predictor was lower initial serum creatinine. This is intuitive, as serum creatinine as a surrogate of renal function is ubiquitous in mortality prediction tools developed for critically ill, cardiac, and PCI‐amenable patients, although a recent analysis did not show statistical significance for creatinine in VA‐ECMO patients with CS . Accordingly, 38.7% of patients required renal replacement therapy.…”
Section: Discussionmentioning
confidence: 99%
“…While there were several variables on univariate analysis suggestive of 30‐day survival in our study such as BMI, serum creatinine, platelet count, and SYNTAX score, the only measured multivariable predictor was lower initial serum creatinine. This is intuitive, as serum creatinine as a surrogate of renal function is ubiquitous in mortality prediction tools developed for critically ill, cardiac, and PCI‐amenable patients, although a recent analysis did not show statistical significance for creatinine in VA‐ECMO patients with CS . Accordingly, 38.7% of patients required renal replacement therapy.…”
Section: Discussionmentioning
confidence: 99%
“…23 Serum lactate levels are widely used as a marker of altered tissue perfusion in critically ill patients or those with acute decompensated HF. [24][25][26][27] Both elevated lactate levels and lactate clearance during ECMO therapy in cardiogenic shock are predictive markers for mortality. 4,25 LA venting allows for the unloading of the LVD and increases the chances of myocardial recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Lactate is a metabolic product of anaerobic glycolysis reflecting inadequate oxygen delivery to the peripheral tissue, thus, suggesting abnormal cellular oxygen metabolism 23 . Serum lactate levels are widely used as a marker of altered tissue perfusion in critically ill patients or those with acute decompensated HF 24‐27 . Both elevated lactate levels and lactate clearance during ECMO therapy in cardiogenic shock are predictive markers for mortality 4,25 .…”
Section: Discussionmentioning
confidence: 99%
“…Thomas Fux et al of the Karolinska Institute, Stockholm, Sweden reported on preimplant predictors for the use of venoarterial extracorporeal membrane oxygenation (VA‐ECMO) in refractory cardiogenic support (RCS). They retrospectively analyzed 76 consecutive patients supported with VA‐ECMO due to RCS.…”
Section: Cardiopulmonary Support and Membrane Oxygenationmentioning
confidence: 99%